2014
DOI: 10.1007/s10950-014-9471-y
|View full text |Cite
|
Sign up to set email alerts
|

The 2012 Emilia (Northern Italy) earthquake sequence: an attempt of historical reading

Abstract: In May-June 2012, the Po Valley (Northern Italy) was struck by an earthquake sequence whose strongest event occurred on 20 May (Mw 5.9). The intensity values (Imax 7-8 EMS98) assessed through macroseismic field surveys seemed inappropriate to describe the whole range of effects observed, especially those to monumental heritage, which suffered very heavy damage and destruction. The observed intensities in fact were significantly lower than those we could have expected after a Mw 5.9 event for Italy. As magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Moderate to large earthquakes are infrequent in this area, which is characterized by a low‐to‐moderate level of seismicity as compared to Central and Southern Italy. It has remained almost silent since the M 5.5 1570 Ferrara earthquake, with the exception of sporadic small‐ to medium‐magnitude earthquakes [ Graziani et al , ]. This long return period results from a slow strain rate (north‐south shortening of ~1 mm/yr) [ Maesano et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Moderate to large earthquakes are infrequent in this area, which is characterized by a low‐to‐moderate level of seismicity as compared to Central and Southern Italy. It has remained almost silent since the M 5.5 1570 Ferrara earthquake, with the exception of sporadic small‐ to medium‐magnitude earthquakes [ Graziani et al , ]. This long return period results from a slow strain rate (north‐south shortening of ~1 mm/yr) [ Maesano et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Even the comparison of magnitudes computed by BOXER (Gasperini et al, 1999(Gasperini et al, , 2010 using the intensity estimates made by the two scales shows a substantial coincidence (Table 2 and Table S1 of the supplemental material). This means that, apart from the data reported in the paper by Graziani et al (2015), EMS and MCS intensities estimated in Italy appear substantially equivalent.…”
Section: Comparison Between Ems and Mcs Intensitiesmentioning
confidence: 65%
“…If EMS and MCS were equivalent, intensities should coincide with each other, at least on average. Graziani et al (2015) found instead that EMS are smaller than MCS (OTC) by 0.6 degrees on average. Moreover, the macroseismic magnitude computed by BOXER (Gasperini et al, 1999(Gasperini et al, , 2010 using EMS is 0.28 m.u.…”
Section: Comparison Between Ems and Mcs Intensitiesmentioning
confidence: 80%
See 2 more Smart Citations